2017
DOI: 10.1002/jssc.201601255
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Characterization of the major chemical constituents from Polygoni Multiflori Caulis by liquid chromatography tandem mass spectrometry and comparative analysis with Polygoni Multiflori Radix

Abstract: Polygoni Multiflori Caulis is a traditional Chinese medicine that has been used for a long time to treat sleep disorders. However, the multiple chemical composition analysis has not been reported. In this study, a simple, rapid and effective ultra-high performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry method was established to characterize the components of Polygoni Multiflori Caulis. In addition, a chemical comparative analysis was performed with Polygoni Multiflori Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Dianthrones as secondary metabolisms resulted from the reduction product of anthraquinones in plant biosynthesis pathways 10 . Previous studies 14,27,28 showed that anthraquinones were the major constituents of PMC, which could revert to corresponding anthrones. Subsequently, dianthrones could be obtained by an oxidative coupling reaction of two anthrones by taking off 2H through C10–C10′ bond.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dianthrones as secondary metabolisms resulted from the reduction product of anthraquinones in plant biosynthesis pathways 10 . Previous studies 14,27,28 showed that anthraquinones were the major constituents of PMC, which could revert to corresponding anthrones. Subsequently, dianthrones could be obtained by an oxidative coupling reaction of two anthrones by taking off 2H through C10–C10′ bond.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, minor dianthrone glycosides 9–11 isolated from PMR via phytochemical methods have proved the obvious toxicity related to liver damage 12,13 . Though, PMC and PMR come from the different parts of PM, phytochemical investigations indicate that PMC has similar main constituents in common with PMR such as anthraquinones, stilbene and flavonoids 14 . However, there has been a lack of study on dianthrones in PMC.…”
Section: Introductionmentioning
confidence: 99%
“…As the content of the four components greatly differed between Polygonum multiflorum Radix and Polygoni multiflori Radix Preaparata samples obtained from different production areas, it was difficult to use a concrete content limit to differentiate Polygonum multiflorum Radix from Polygoni multiflori Radix Preaparata, which is a drawback and has remained unsolved previously. Through a mass data analysis in 2016, the “ Polygonum multiflorum rules” theory was proposed for the first time in a thesis [25], and the F value was used to differentiate Polygonum multiflorum Radix from Polygoni multiflori Radix Preaparata. As four control samples, emodin, physcion, emodin-8-O- β -D-glucopyranoside, and physcion-8-O- β -D-glucopyranoside, were used in this method, it had disadvantages such as high cost and complicated operations; in addition, the limit value was set as 1, which caused misjudgment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have analyzed the quality of Polygonum multiflorum Radix based on the relationship among 2,3,5,4′-tetrahydroxy diphenyl ethylene-2-O- β - glucoside, combined anthraquinones, and calcium oxalate [17] by determining the contents of glucosides and combined anthraquinones in Polygonum multiflorum Radix using HPLC-DAD [18]; determining the contents of 2,3,5,4′- tetrahydroxy diphenyl ethylene-2-O- β - glucoside, emodin, and emodin monemethyl ether in Polygonum multiflorum Radix and its residues using HPLC [19]; determining the contents of five anthraquinones, aloe-emodine, rheine, emodine, chrysophanol, and physcione in Polygonum multiflorum using HPLC [20]; determining the contents of four phenols, gallic acid, trans-2,3,5,4′-tetrahydroxystilbene-2-O- β -D-glucopyranoside, emodin, and emodin-8-O- β -D-glucopyranoside in Polygonum multiflorum and its processed form using UHPLC-MS/MS [21]; determining the contents of 2,3,5,4′-tetrahydroxystilbene-2-O- β -D-glucoside, emodin-8-O- β -D-glucoside, emodine, and physcion using LC-VWD-MS, UPLC-PDA, and HPLC-PAD [2224] comparing the compositions of Polygonum multiflorum Thunb. and Polygonum multiflorum Radix using UHPLC-Q-TOF-MS [25]; and determining the 14 main components of Polygonum multiflorum Radix collected from different areas as well as the amounts of stibene glucosides, phenolic acids, flavones, and anthraquinones present in Polygonum multiflorum Radix using LC-MS/MS [26, 27]. One study showed that after processing of Polygonum multiflorum Radix, the contents of two anthraquinones, emodin-8-O- β -D-glucopyranoside and emodin monemethyl ether-8-O- β -D-glucopyranoside, were decreased in Polygoni multiflori Radix Preaparata, but the contents of emodin and emodin monemethyl ether increased [28–30].…”
Section: Introductionmentioning
confidence: 99%
“…The role of PM has been investigated in various biological activities, including antioxidant activity, nerve cell protection, lipid regulation, and hair-follicle growth [10,11]. Furthermore, PM has been used for a long time as an antiageing agent [12]. However, the adverse effects of PM, such as hepatotoxicity, skin allergy, and bleeding in the upper digestive tract, have been reported occasionally [13,14].…”
Section: Introductionmentioning
confidence: 99%